BUDAYA DAN KESEHATAN (Suatu Tinjuan Psikologi) - Lerik, Mariana Dinah Ch. (Pergizi Pangan DPD NTT, 2010)
Culture is one of the factors that affect ones’ health. The writer reviews the difference of culture in identifying health, social-cultural effect at psychology disorder and abnormal behaviour, the effect of socio-cultural on physical health and medication process of disease, culture difference in healing disease, cultural difference in psychotherapy and psychological measurement.